Shear-thinning dynamics and viscoelasticity of a novel Eremurus spectabilis glucomannan: Structural insights and implications for food/pharmaceutical applications - Zahra Hoseinpour; Razieh Niazmand; Mahmut Ekrem Parlak; Mojtaba Heydari-Majd; Furkan Türker Saricaoglu (Carbohydrate Polymer Technologies and Applications, 2025)
This study aimed to isolate, purify, and characterize the principal water-soluble polysaccharide (ESRP) from E. spectabilis roots and evaluate its structural, thermal, emulsifying, and rheological properties. ESRP exhibited notable in vitro phenolic content and DPPH radical scavenging abilities. Thermal analysis via DSC revealed superior thermal stability, while FT-IR analysis indicated the presence of β-pyranose configuration in its main polysaccharide backbone. GC–MS and analyse revealed a composition of d-glucose (42.77 %), d-mannose (52.82 %), and d-galactose (4.43 %) and presence of degree of O-acetyl groups with a molecular weight of 19.1 kDa. The Zeta potential was negative (–20.97 mV), indicating an anionic nature of ESRP. The aqueous ESRP solutions showed shear thinning behaviour, with viscosity dependent on concentration and temperature. ESRP solutions exhibited pseudo-plastic properties, with lower moduli values compared to inulin. Overall, these findings suggest that ESRP, as a shear-thinning substance, has potential as a novel stabilizer or thickener in various industrial applications.